Genome-wide identification of allele-specific expression in response to Streptococcus suis 2 infection in two differentially susceptible pig breeds - Huayu Wu (2018)
© 2015, Institute of Plant Genetics, Polish Academy of Sciences, Poznan. Although allele expression imbalance has been recognized in many species, and strongly linked to diseases, no whole transcriptome allele imbalance has been detected in pigs during pathogen infections. The pathogen Streptococcus suis 2 (SS2) causes serious zoonotic disease. Different pig breeds show differential susceptibility/resistance to pathogen infection, but the biological insight is little known. Here we analyzed allele-specific expression (ASE) using the spleen transcriptome of four pigs belonging to two phenotypically different breeds after SS2 infection. The comparative analysis of allele specific SNPs between control and infected animals revealed 882 and 1096 statistically significant differentially expressed allele SNPs (criteria: ratio≧2 or ≦0.5) in Landrace and Enshi black pig, respectively. Twenty nine allelically imbalanced SNPs were further verified by Sanger sequencing, and later six SNPs were quantified by pyrosequencing assay. The pyrosequencing results are in agreement with the RNA-seq results, except two SNPs. Looking at the role of ASE in predisposition to diseases, the discovery of causative variants by ASE analysis might help the pig industry in long term to design breeding programs for improving SS2 resistance.